Influence of silver nanoparticles conditions synthesis on their electrochemical properties; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Perevezentseva D. O. Dariya Olegovna; Gorchakov E. Eduard; Petrushin M. Maksim; Hismutdinov I. Ilya; Bimatov V. Vladimir (Synthesis and physicochemical characteristics of materials, 2016)
Title screen